(untitled) (Economics and region, 2019)
The essence and content of business processes management on the basis of the logistic concept of enterprise innovative development was disclosed in the work. Peculiarities of business processes reengineering on the enterprise in the context of its innovative development were investigated. Business processes (basic, auxiliary, processes of development, management) study of which provides realization of the logistic conception of enterprises innovative development were investigated in this article